Effectiveness and safety of acupuncture for post-stroke spasticity: A systematic review and meta-analysis - Xue, Chen; Jiang, Chengzhi; Zhu, Yuanyuan; Liu, Xiaobo; Zhong, Dongling; Li, Yuxi; Zhang, Huiling; Tang, Wenjing; She, Jian; Xie, Cheng; Li, Juan; Feng, Yue; et al. (Frontiers in Neurology, 2022)
Objectives: This systematic review and meta-analysis aimed to comprehensively evaluate the effectiveness and safety of acupuncture for post-stroke spasticity. Methods: Nine electronic databases were searched from their inception to March 3rd, 2022, to identify randomized controlled trials (RCTs) that investigated the effectiveness and safety of acupuncture for post-stroke spasticity. Two reviewers independently screened the studies, extracted the data, and assessed the risk of bias. RevMan 5.4 and R 4.2.0 software were utilized for statistical analysis. Results: A total of 85 eligible studies were included, involving 6,248 individuals. The pooled data demonstrated that acupuncture combined with conventional rehabilitation (CR) was superior to CR in reducing the Modified Ashworth Scale (MAS) score (SMD = −0.71; 95%CI = −0.81 to −0.61; P <0.00001; I2 =64%). The favorable results were also observed when compared acupuncture with CR (SMD = −0.22, 95%CI = −0.36 to −0.07; P = 0.004; I2 =49%). Subgroup analyses showed that acupuncture combined with CR had a better therapeutic effect than CR in patients with MAS score ≥ three. Acupuncture treatment with a frequency of once a day was more effective than acupuncture once every other day. In addition, the antispasmodic effect increased with more sessions of acupuncture treatment. Three studies explicitly reported slight acupuncture-related adverse events. The certainty of the evidence for MAS score of acupuncture vs. CR was moderate, and MAS score of acupuncture plus CR vs. CR was low. Conclusions: Acupuncture could be recommended as adjuvant therapy for spasticity after stroke. However, due to the poor methodological quality of included RCTs and high heterogeneity, the effectiveness and optimal protocol of acupuncture for post-stroke spasticity remain to be confirmed.